Japan Administered Account for Selected IMF Activities (JSA) : Annual Report Fiscal Year 2003. (International Monetary Fund, 2004)
This paper discusses Fiscal Year 2003 Annual Report for Japan Administered Account for Selected IMF Activities (JSA). The report consists of a brief description of the IMF and its activities, with a particular focus on its technical assistance activities. It provides greater detail with regard to the JSA and the scholarship programs. It also describes the objectives, size and scope, and use with a focus on fiscal year 2003. The report highlights that in FY2003, JSA financing accounted for 18 percent of total IMF technical assistance, 33 percent of the assistance delivered in the field, and 66 percent of the total external financing.